Faktor-Faktor Daya Beli Dan Kepuasan Belanja Online Selama Pandemi Covid-19 di Kalangan Millenial - Ribka Agustina; Bayu Seno Pitoyo; Dody Kurniawan (Jurnal Kajian Ilmiah, 2022)
The purpose of this study was to analyze product prices, service quality, and trust in the ability of the Jakarta Millennial community to shop online and shoppers during the Covid19 pandemic. This sample collector has 100 index statements with statement metrics that include variables that look at product prices, service quality, purchasing power and trust in satisfaction when shopping online during the Covid-19 pandemic at Shopee. Use a survey that asks the respondent 28 questions. Sampling by random sampling method using multiple linear regression method. The results show that fluctuations in product prices, service quality, and trust during the Covid19 pandemic simultaneously have a partial positive impact on the purchasing power and online shopping satisfaction of the Millennial community in Jakarta.